2021
DOI: 10.1039/d0lc01135e
|View full text |Cite
|
Sign up to set email alerts
|

Multi-oscillation microrheology via acoustic force spectroscopy enables frequency-dependent measurements on endothelial cells at high-throughput

Abstract: Active microrheology is one of the main methods to determine the mechanical properties of cells and tissue, and the modelling of these viscoelastic properties is under heavy debate with many...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 53 publications
(41 reference statements)
0
37
0
Order By: Relevance
“…Human umbilical vein endothelial cells (HUVECs) were a kind gift from Prof. Dr. V. Gerke (Institute of Medical Biochemistry, University of Münster, Germany). The cells were cultured in 60 mm diameter polystyrene dishes (Corning CellBIND Surface 60 mm Culture Dish, Corning) in culture medium consisting of two equal parts of Endothelial Cell Growth Medium 2 (PromoCell) containing its according supplements (Growth Medium 2 SupplementMix, PromoCell) and of Medium 199 Earle's (F0615, Biochrom GmbH or M2154, Sigma-Aldrich) with 2.2 g/l NaHCO 3 , without L-glutamine supplemented with 10 % fetal bovine serum (F7524, Sigma-Aldrich), 0.2 units/ml heparin (H3149, Sigma), 30 µg/ml gentamicin (gibco) and 15 µg/ml amphotericin B (gibco) as previously described [46]. Culture dishes were placed in a humidified incubator at 37 • and 5 % CO 2 .…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs) were a kind gift from Prof. Dr. V. Gerke (Institute of Medical Biochemistry, University of Münster, Germany). The cells were cultured in 60 mm diameter polystyrene dishes (Corning CellBIND Surface 60 mm Culture Dish, Corning) in culture medium consisting of two equal parts of Endothelial Cell Growth Medium 2 (PromoCell) containing its according supplements (Growth Medium 2 SupplementMix, PromoCell) and of Medium 199 Earle's (F0615, Biochrom GmbH or M2154, Sigma-Aldrich) with 2.2 g/l NaHCO 3 , without L-glutamine supplemented with 10 % fetal bovine serum (F7524, Sigma-Aldrich), 0.2 units/ml heparin (H3149, Sigma), 30 µg/ml gentamicin (gibco) and 15 µg/ml amphotericin B (gibco) as previously described [46]. Culture dishes were placed in a humidified incubator at 37 • and 5 % CO 2 .…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Oscillatory microrheology fixes the timescale of the perturbation according to the applied frequency, while the other tests probe a superposition on many timescales in a single test. This has the advantage that the frequency-dependency of the material response can be measured directly and that the measurement frequency can be adopted to the frequency range of interest [52]. However, timeand frequency-domain data are mathematical equivalents and time-domain data of the cells viscoelastic response can even be directly transformed into the frequency domain [53].…”
Section: Discussionmentioning
confidence: 99%
“…This is essential as Nguyen et al. extensively showed that the force distribution in the chip can vary depending on the position of the bead ( Nguyen et al., 2021 ). The spatial calibration map (n = 20 beads) for our field of view obtained by performing the Stokes force calibration is shown in Figure S2 .…”
Section: Methodsmentioning
confidence: 99%